Mental Health is a Verb A Pocket Guide to Mental Health for Nursing Students - Bush, Jake; Van Der Like, Jill (Open textbook library., 2024)
MENTAL HEALTH IS A VERB is an open education resource written by Jake Bush, Ph.D., RN, CNE, and Jill Van Der Like, DNP, MSN, RNC through the University of West Florida which addresses mental health nursing care. The book opens with a foundational module that provides a brief history of mental health treatment, pertinent theorists, and the underpinning concepts of mental health versus mental illness, followed by a separate chapter on psychopharmacology. The heart of the text is arranged into the most common mental health diagnoses. Additionally, this second edition includes the addition of case studies (modules 8-19), two virtual simulation activities (modules 7 and 13), and a mental health cumulative study guide as an appendix.